Inventarisasi Keanekaragaman Flora sebagai Upaya Konservasi di Kawasan PLTA Way Besai, Lampung Barat - Khoryfatul Munawaroh; Rizki Kurnia Tohir; Vilda Puji Dini Anita; Mhd Muhajir Hasibuan; Tafdhilah Tartil; Akbar Ash Shiddiqi Faedloni; Ari Setyawan; Daliilah Haniifah Azhaar; Ruben Christoper; Ricky Johanes; Sumitro Pandapotan; Agung Abdul Aziz (Biocaster : Jurnal Kajian Biologi, 2026)
The Way Besai Hydroelectric Power Plant (PLTA) is located in West Lampung Regency, Lampung Province, with a capacity of 90.4 MW and utilizes water from the Way Besai River. The availability of stable water discharge is highly dependent on the vegetation conditions in the catchment area. This study aims to examine the diversity of flora and vegetation sustainability in the Way Besai hydropower plant area using an exploration method divided into six observation lines. The results showed that there were 57 types of plants belonging to 21 families. The most common species are sonokeling (Dalbergia latifolia) with 140 individuals and seripit (Crypteronia paniculata) with 113 individuals. The families with the highest number of species are obtained from the families Moraceae and Fabaceae. The types of the Moraceae family are dominated by Ficus spp., which acts as a source of animal feed, while from the Fabaceae family, there are more types of multipurpose plants (MPTS). The diversity of species and evenness of flora around the Way Besai hydropower plant is relatively high, as shown by the diversity index value (H') of 3.281 and the evenness index value (E) of 0.812. Although this value is relatively high, the maintenance and conservation of flora still needs to be carried out intensively to maintain the stability of the water discharge of the Way Besai River. These results confirm that the vegetation around the Way Besai hydropower plant is still relatively sustainable, but sustainable conservation efforts are needed to control land conversion that has the potential to reduce the water discharge of the Way Besai River.